Redefining the Baseline: Reasonable Efforts, Family Preservation, and Parenting Foster Children in New York - Bonagura, Rebecca (Columbia Journal of Gender and Law, 2008)
Adolescents in New York’s foster care system are having children at higher rates and at younger ages than other teens. As one of the largest municipal foster care systems in the United States, New York City’s Administration for Children’s Services (ACS) is grappling with the challenge of responding to the particular needs of young parents who are raising children within the state foster care system (whom this article will refer to as parenting wards), rather than within an extended family. Although New York does not track either the number of foster children who are parents or the age of respondents to removal petitions, the office of the Public Advocate for the City of New York has reported that one in every six girls in foster care in New York City is either pregnant or parenting, a statistic that is likely an underestimate. The high frequency of parenting among teens in the foster care system is representative of national trends. Teen girls in foster care are two and a half times more likely to become pregnant before their nineteenth birthdays than teens that are not in foster care. Parents under eighteen years old are also more likely to be charged with child abuse or neglect than those who wait until they are older to have children, and they are more likely to have their children removed by the state. The complicated reality behind these numbers is that because of state failure to provide the placements, services, and support necessary to function successfully as a family, parenting wards and their children are often denied the opportunity to remain together. This failure is avoidable. The state should articulate and implement the idea that, as the caretaker of foster children and the enforcer of child welfare laws, it has a heightened duty to families of parenting wards before and after removal proceedings begin.